Paraorosius, a new genus of leafhopper (Hemiptera: Cicadellidae: Deltocephalinae: Opsiini), with description of a new species from the Middle East - El-Sonbati, S. A.; Wilson, M. R.; Dhafer, H. M. Al (Zootaxa, 2016)
A new genus, of the leafhopper tribe Opsiini, Paraorosius is proposed to accommodate Orosius minuicus Dlabola, 1979 and, P. hanii sp. n. from the Kingdom of Saudi Arabia. A key to the genera of Opsiini of the Arabian Peninsula is provided.